Acute Stroke in Times of the COVID-19 Pandemic: A Multicenter Study - Hoyer, Carolin; Ebert, Anne; Huttner, Hagen B; Puetz, Volker; Kallmünzer, Bernd; Barlinn, Kristian; Haverkamp, Christian; Harloff, Andreas; Brich, Jochen; Platten, Michael; Szabo, Kristina (Stroke (1970), 2020)
This study aims to assess the number of patients with acute ischemic cerebrovascular events seeking in-patient medical emergency care since the implementation of social distancing measures in the coronavirus disease 2019 (COVID-19) pandemic. In this retrospective multicenter study, data on the number of hospital admissions due to acute ischemic stroke or transient ischemic attack and numbers of reperfusion therapies performed in weeks 1 to 15 of 2020 and 2019 were collected in 4 German academic stroke centers. Poisson regression was used to test for a change in admission rates before and after the implementation of extensive social distancing measures in week 12 of 2020. The analysis of anonymized regional mobility data allowed for correlations between changes in public mobility as measured by the number and length of trips taken and hospital admission for stroke/transient ischemic attack. Only little variation of admission rates was observed before and after week 11 in 2019 and between the weeks 1 and 11 of 2019 and 2020. However, reflecting the impact of the COVID-19 pandemic, a significant decrease in the number of admissions for transient ischemic attack was observed (-85%, -46%, -42%) in 3 of 4 centers, while in 2 of 4 centers, stroke admission rates decreased significantly by 40% and 46% after week 12 in 2020. A relevant effect on reperfusion therapies was found for 1 center only (thrombolysis, -60%; thrombectomy, -61%). Positive correlations between number of ischemic events and mobility measures in the corresponding cities were identified for 3 of 4 centers. These data demonstrate and quantify decreasing hospital admissions due to ischemic cerebrovascular events and suggest that this may be a consequence of social distancing measures, in particular because hospital resources for acute stroke care were not limited during this period. Hence, raising public awareness is necessary to avoid serious healthcare and economic consequences of undiagnosed and untreated strokes and transient ischemic attacks.